Diffusion tensor imaging in determining atypical peripheral nerve neuroma in a patient with a painless mass - Ahmad Saad, Fathinul Fikri; Fathinul Fikri, Razinul Syamim; Ahmad Shahrir, Ahmad Danial (AVES Yayincilik, 2024)
Difusion tensor imaging (DTI) promises further scrutiny in determining the functional and structural defects of the afected peripheral nerves (PNs) via diferences in nerve stifness and information of early regeneration. The report by Zhang et al1 in their study on DTI of axonal and myelin changes in classical trigeminal neuralgia has substantiated that significantly increased fusion anisotropy (FA) is sufciently sensitive to diferent pathologic states. In this regard, we emphasize that the reliability of the functional metric of the demyelination in peripheral neuropathy has more favorable credit than conventional difusion-weighted imaging (DWI) in understanding patients with atypical presentations of the causative factors of peripheral neuropathy. We presented a case of a 71-year-old man who presented with a painless, protracted subcutaneous tissue lump on the medial side of his left forearm, with associated numbness over the first and second web space. The lump was soft and non-tender, with a negative Tinel’s sign on examination. Difusion tensor imaging scanning protocols were performed on the 3.0 T scanner (Prisma, Siemens Healthineers, Erlangen, Germany), consisting of 13 volumes (45 slices, 128 × 128 voxel, slice thickness 2.2 mm, in-plane voxel size 1.5 mm × 1.5 mm), representing 12 gradient directions and 1 scan with gradient 0 (B0) centered at the left wrist. Echo time (TE) and repetition time (TR) were 93 ms and 8000 ms, respectively. B value was 800 s/mm2, 5 scans were k-space averaged online by the Siemens SYNGO operating software. A T1-weighted magnetization-prepared rapidacquisition gradient echo sequence consisting of 160-200 sagittal partitions depending on head size was used. Written informed consent was obtained from the patient who agreed to take part in the study.